The Buenos Aires affair: parodia y puesta en abismo. Olvido de amor no correspondido. - Camacho Ramírez., Raimy (2012)
This article demonstrates that there exist a connection between epigraphs and the plot in the novel The Buenos Aires Affair by Manuel Puig. The bond mentioned above is called “mise en abyme” which means that paragraphs and the action of the story show some features in common. We will analyse two features: In one hand, the use of the proper noun by itself; and, on the other hand, his omission. This two facts help to built up the parodic contrast between the main character, Gladys Hebe Onofrio, and the film stars in the epigraphs.